Role of transformational leadership and perceived organizational support in promoting innovation among Malaysian Academics - Ebrahim, Zarina Begum; Ismail, Irzan; Kassim, Erne Suzilah (International Journal of Accounting, Finance and Business, 2025)
This research examines the impact of Transformational Leadership (TL) and Perceived Organisational Support (POS) on Innovative Work Behaviour (IWB) among academic staff in Malaysian universities. The research investigates the effects of leadership and organizational support on innovation in academic settings using data from 338 permanent academics employed in Malaysian HEIs listed in the QS World Rankings 2023. Academic staff members demonstrate significant levels of innovative behaviour, especially when it comes to creating and executing new ideas, according to the study's descriptive and reliability analyses, which are underpinned by Social Exchange Theory (SET). However, there are obstacles when it comes to promoting and campaigning for these innovations. POS is generally good, but there are some shortcomings when it comes to acknowledging additional work and resolving staff issues. Meanwhile, Transformational leadership is crucial in creating a constructive and cooperative atmosphere that stimulates innovation. The results indicate that enhancing leadership skills, ensuring regular acknowledgment, and cultivating a more robust culture of innovation can markedly enhance IWB among academic staff. The study provides actionable and managerial insights for university administrators to formulate policies that foster innovation, resulting in enhanced academic achievement and institutional advancement.